“I feel sad”: Students’ voices on lecturer’s feedback on Google Docs - Kurniawati, Atin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
Students’ responses to teacher’s feedback can affect their emotions and attitude toward tasks they are working with. Amidst the growing use of digital tools in facilitating English writing classes, this current article explores students’ emotions and their attitude toward teacher’s feedback given to their writing tasks on Google Docs. This descriptive qualitative study gathered data through a questionnaire from twenty-three university students majoring in English Education Department and semi-structured interviews with three students. The questionnaire consisted of closed and open-ended questions to elicit information about the students’ responses to teacher’s feedback. Meanwhile, the semi-structured interviews were conducted for further investigation as well as to provide data source triangulation. The data were analyzed thematically by identifying the themes from the groups of data which correspond to the research questions. The findings revealed that the students experienced two kinds of emotions, either positive emotion (curious and happy) or negative emotion (sad and confused). Their emotions were influenced by the students’ expectation, lower proficiency levels, and their learning commitment while their positive emotions were from their self-efficacy in the learning process, higher proficiency level, and higher learning motivation. These emotions contributed to their attitude in the writing class. The students with positive emotions tend to commit to the task dan do revision, but negative emotions didn’t encourage them to reflect on the feedback and do revision. Moreover, Google Docs was typically used for asynchronous tasks that they couldn’t directly confirm or clarify their understanding. Several implications and suggestions are also discussed.